1983
DOI: 10.1152/ajpregu.1983.245.6.r843
|View full text |Cite
|
Sign up to set email alerts
|

Uterine blood flow in relation to endogenous hormones during estrous cycle and early pregnancy

Abstract: To evaluate the extent to which endogenous hormones in peripheral blood can account for uterine blood flow (UBF), rates of blood flow and concentrations of estrone (E1), estradiol (E2), and progesterone (P4) were measured simultaneously in four sheep during the estrous cycle and the first 3 wk of pregnancy. During the estrous cycle, UBF was inversely related to the concentration of P4 (P less than 0.01) and directly related to (E1 + E2)/P4 (P less than 0.01). There was no animal in which UBF was related to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…Given in pharmacological doses, this hormone will induce overgrowth of caruncles (Alexander & Williams, 1966) and growth of uterine blood vessels (Phelps, 1946;Williams, 1948;Caton et al, 1974a) and does affect regulation of uterine blood flow (Caton et al, 1974a;Caton, Abrams, Lackore, James & Barron, 1974b;Caton et al, 1980;Roman-Ponce, Caton, Thatcher & Lehrer, 1983). Ewes differ with respect to the amount of progestagen released per kg of fetal, placental and uterine tissues during the last weeks of pregnancy and this amount is proportional to the subsequent weight of the lamb (Caton, Kalra & Wilcox, 1983).…”
Section: Chronic Experimentsmentioning
confidence: 99%
“…Given in pharmacological doses, this hormone will induce overgrowth of caruncles (Alexander & Williams, 1966) and growth of uterine blood vessels (Phelps, 1946;Williams, 1948;Caton et al, 1974a) and does affect regulation of uterine blood flow (Caton et al, 1974a;Caton, Abrams, Lackore, James & Barron, 1974b;Caton et al, 1980;Roman-Ponce, Caton, Thatcher & Lehrer, 1983). Ewes differ with respect to the amount of progestagen released per kg of fetal, placental and uterine tissues during the last weeks of pregnancy and this amount is proportional to the subsequent weight of the lamb (Caton, Kalra & Wilcox, 1983).…”
Section: Chronic Experimentsmentioning
confidence: 99%
“…Using intact ewes, Greiss and Anderson [12] reported that UBF is elevated during the periovulatory period in association with behavioral receptivity to a ram. Ford et al [13][14][15][16] and Roman-Ponce et al [17] reported that the higher the estrogen/progesterone (P 4 ) ratio in intact animals, the greater the magnitude of UBF. However, in studies using cycling cows, ewes, and sows, the timing and magnitude of the pattern of UBF of individual animals was quite variable [16,17] compared with very low, nearly nonexistent variability in the ovx model.…”
Section: Introductionmentioning
confidence: 99%
“…Ford et al [13][14][15][16] and Roman-Ponce et al [17] reported that the higher the estrogen/progesterone (P 4 ) ratio in intact animals, the greater the magnitude of UBF. However, in studies using cycling cows, ewes, and sows, the timing and magnitude of the pattern of UBF of individual animals was quite variable [16,17] compared with very low, nearly nonexistent variability in the ovx model. While this made the ovx model a vastly predictable and easier model to study than the intact sheep, it may not, however, represent what is actually occurring in the uterus during the estrous cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Variations in uterine blood flow in cycling mares have been attributed to changes in circulating estrogen concentrations. However, due to a weak correlation between the resistance to uterine blood flow and plasma estrogen concentrations, other factors may also regulate uterine blood flow [2].Changes in uterine blood flow during the estrous cycle in many species are mediated mainly by estrogens [5]; although flow was enhanced by high plasma estradiol concentrations [6,7] and decreased during the luteal phase [8,9], the mechanisms involved have not been elucidated. Estrogens appear to act via two pathways: the genomic and non-genomic pathways [10].…”
mentioning
confidence: 99%
“…Changes in uterine blood flow during the estrous cycle in many species are mediated mainly by estrogens [5]; although flow was enhanced by high plasma estradiol concentrations [6,7] and decreased during the luteal phase [8,9], the mechanisms involved have not been elucidated. Estrogens appear to act via two pathways: the genomic and non-genomic pathways [10].…”
mentioning
confidence: 99%